Energy expenditure of patients on ECMO: A prospective pilot study. Issue 3 (6th November 2018) - De Waele, Elisabeth; Jonckheer, Joop; Pen, Joeri J.; Demol, Joy; Staessens, Kurt; Puis, Luc; La Meir, Mark; Honoré, Patrick M.; L. N. G. Malbrain, Manu; Spapen, Herbert D.
Abstract : Background: An optimal nutritional approach sustained by convenient monitoring of metabolic status and reliable assessment of energy expenditure (EE) may improve the outcome of critically ill patients on extracorporeal membrane oxygenation (ECMO). We previously demonstrated the feasibility of indirect calorimetry (IC)—the standard of care technique to determine caloric targets—in patients undergoing ECMO. This study aims to compare measured with calculated EE during ECMO treatment. We additionally provide median EE values for use in settings where IC is not available. Methods: IC was performed in seven stable ECMO patients. Gas exchange was analyzed at the ventilator, and ECMO side and values were introduced in a modified Weir formula to calculate resting EE. Results were compared with EE calculated with the Harris‐Benedict equation and with the 25 kcal/kg/day ESPEN recommendation. Results: Total median oxygen consumption rate was 196 (Q1‐Q3 158‐331) mL/min, and total median carbon dioxide production was 150 (Q1‐Q3 104‐203) mL/min. Clinically relevant differences between calculated and measured EE were observed in all patients. The median EE was 1334 (Q1‐Q3 1134‐2119) kcal/24 hours or 18 (Q1‐Q3 15‐27) kcal/kg/day. Conclusion: Compared with measured EE, calculation of EE both over‐ and underestimated caloric needs during ECMO treatment. Despite a median EE of 21 kcal/kg/day, large variability in metabolic rate was found and demands further investigation.